Long-Term High-Intensity Plyometric Training Increases Muscle Strength and Power of The Lower Body in Young Healthy Males - Slamet Raharjo; Nguyen Tra Giang; Raja Mohammed Firhad Raja Azidin; Mustika Fitri; Mahmud Yunus; Ramdan Pelana (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to effect of long-term high-intensity plyometric training on the strength and power of the lower body muscles in young healthy males. A total of 40 healthy men, aged 20–24 years, with no history of chronic disease, were recruited to become research subjects and were divided into 2 groups: the control group (CTRL; n=20) and the high-intensity plyometric training group (HIPT; n=20). The intervention was carried out for six weeks, with a frequency of four times per week. Meanwhile, at CTRL, no special training is given. Measurements of muscle strength and power were carried out between the pretest and posttest. The data analysis technique uses a paired sample t-test with a significance level of 5%. The results showed the average muscle strength between the pretest and posttest on CTRL (117.75±19.39 to 118.55±16.27 kg, p=0.704), and HIPT (116.55±19.64 to 132.25±19.15 kg, p=0.000). Muscle power between the pretest and posttest on CTRL (52.10±6.95 to 52.70±6.53 cm, p=0.055), and HIPT (53.05±6.72 to 66.85±8.07 cm, p=0.000). This research proves that long-term high-intensity plyometric training increases lower-body muscle strength and power in healthy young males.